Strengthening Community Health Resilience: Hypertension and Diabetes Education, Local Herbal Drink Training, and Natural Handwash Production in Sukabumi - Wulan Tri Wahyuni; Ulfiatun Nisa; Irmanida Batubara; Trivadila Wahyuni; Eka Widya Nugraha; Yusuf Ryadi; Waras Nurcholis (Indonesian Journal of Community Engagement, 2026)
This community engagement program aimed to strengthen health resilience among women in Sukabumi by enhancing their understanding of hypertension and diabetes, while also building practical skills in preparing local herbal beverages and natural handwash products. A total of twenty-five PKK members from Karangtengah Village participated in structured educational sessions delivered by medical lecturers, baseline screening of blood pressure and blood glucose levels, and hands-on training utilizing locally available resources. Participants’ knowledge was assessed using matched pre- and post-tests, while behavioural adoption was evaluated through post-intervention self-reports. The screening results revealed that a substantial proportion of participants exhibited elevated blood pressure and/or blood glucose levels, highlighting the relevance and urgency of the program. Significant improvements in knowledge were observed across all assessed domains, including risk factors, early symptoms, preventive lifestyle practices, and recognition of locally available herbal ingredients. All knowledge gains were statistically significant, indicating effective health information transfer. The practical training component further enhanced participants’ confidence and self-efficacy, as reflected by a high intention to adopt the recommended practices in daily life. Overall, the program demonstrated that community-based, participatory health education combined with culturally appropriate practical training can effectively enhance health knowledge, support positive behavioural change, and promote sustainable household health practices in rural communities.